Two Stay Two Stray (TSTS) Learning Model Assisted with Mind Mapping Improving Students’ Social Studies Learning Outcomes - Ekayani, Ni Putu Sawitri; Suarjana, I Made; Jayanta, I Nyoman Laba (Universitas Pendidikan Ganesha, 2020)
This research aimed to analyze the effect of the Two Stay Two Stray (TSTS) learning model assisted with mind mapping media toward social studies learning outcomes in Grade V. The type of this research was a quasi-experimental research design with nonequivalent post-test only controls group design. The population of this research was all of the fifth-grade elementary schools in Cluster I Bangli District, which totaled 7 classes with 138 students. The samples were determined using a simple random sampling technique, totaling 20 students as the experimental group and 30 students as the control group. Data analysis techniques in this research used descriptive statistical analysis techniques and data analysis prerequisite tests. Hypothesis analysis used the t-test polled variance test. The results of the calculation of the average social studies learning outcomes of the experimental group students were 23.15 included in the very high category, while students in the control group had an average value of 17.23 including the moderate category. Based on calculations with the t-test obtained a t-count of 4.89 is greater than the t-table value of 2.010 with a dk of 48, at a significance level of 5%. From the results of the analysis, it can be concluded that the Two Stay Two Stray (TSTS) learning model assisted with mind mapping media has a significant effect on social studies learning outcomes for fifth-grade elementary school students. Therefore, the TSTS learning model assisted with mind mapping media is suitable to be applied to improve students' social studies learning outcomes